A Web Component for Real-Time Collaborative Text Editing - Maanpää, Pekka (My University, 2019)
Real-time collaborative software allows physically distinct people to co-operate by working on a shared application state, receiving updates from each other in real-time. The goal of this thesis was to create a developer tool, which would allow web application developers to easily integrate a collaborative text editor into their applications. In order to remain technology agnostic and to utilize the latest web standards, this product was implemented as a web component, a reusable user interface component built with native web browser features. The main challenge in developing a real-time collaboration tool is the handling of concurrent updates, which might conflict with one another. To tackle this issue, many consistency maintenance algorithms have been presented in the academic literature. Most of these techniques are variations of two main approaches: operational transformation and commutative replicated data types. In this thesis, we reviewed some of these methods and chose the GOTO operational transformation algorithm to be implemented in our component. Besides selecting and implementing an appropriate consistency maintenance technique, the contributions of this thesis include the design of an easy-to-use application programming interface (API). Our solution also fulfills some practical requirements of group editors not covered by the consistency maintenance theory, such as session management and cleaning of the message queue. The created web component succeeds in encapsulating the complexity related to concurrency control and handling of joining peers in the client-side implementation, which allows the application logic to remain simplistic. This open-source product enables software developers to add a collaborative text editor to their web applications by broadcasting the updates provided by an event-based API to participating peers.
Keywords: collaborative software, web components, consistency maintenance, operational transformation